Processamento e Interpretação de Dados Sísmicos de Parasound no Delta Submarino do Amazonas - Matheson, Guisela Santiago Grossmann (2002)
Amazon submarine delta is the main feature of the Amazon shelf. This area is influenced by several energetic forces, such as the large tidal amplitudes, the North Brazilian Current, the Trade Winds and specially by the enormous water discharge from the Amazon River. The delta construction and the sedimentary distribution have been influenced by this factors during the geologic time. In order to understand these aspects, high resolution shallow seismic and sediment cores were used.The main focus of this research was seismic processing and interpretation of Parasound data to which no echo-character classification was yet established. Data was processed using two softwares, SENT of Bremen University and Seismic Unix (SU) of Center for Wave Phenomena of Colorado School of Mines. At the first stage “pass-band” filters were applied in order to reduce noise and improve the quality of seismic signal. Amplitude spectra were constructed to check the signal attenuation when gas is present in sediment. Profile nterpretation was based on sediment grain-size analyses and spectra amplitude. Ten profiles were interpreted, being three of them perpendicular to the coast and others parallel. Interpretation allowed location of gas charged sediment,characterization of geologic features and distinction of echo character.